POLA INTERAKSI ANTARA MASYARAKAT MUSLIM DAN NON MUSLIM DI PULAU KARAM PONDOK KECAMATAN PADANG BARAT KOTA PADANG - Martalingga, Nengsi - (Pendidikan Sosiologi, 2014)
Indonesia people know as social complex system that consist of religion, races, ethnics, and culture in indonesia. In karam pondok island, subdistrict of west padang have society different religion although language and culture does not matter. However, there are never be conflict. This purpose research is descriptive design interaction between muslim society and non muslim society in karam pondok island, subdistrict of west padang.In this research used interaksionisme symbolic teory by George Herbert Mead this research used qualitative approach with descriptive research. This research take 17 people with used snowballing sampling collecting of data used observation, interview, study documentation and unit group analysa. Data miles and huberman There are three analysis data used in this research: reduction data, display data or The result of this research can conclude that interected design between muslim society and non muslim society. It can two from different form of assosiative and form of disasosiative, form of assosiative is cooperation like mutual aid and form of disasosiative is competition in level legislative conflict church building.